Advanced Real Time Bone Fracture Monitoring with Pain Control Mechanism - Logasundari.T; Gopika.TP; Swathe. L; Saathvika. R (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Bones provide structural aid to the frame, and bone fracture recuperation is crucial for regaining functionality and mobility. The boundaries of traditional external fixators in bone fracture remedy, characterized by a loss of actual-time monitoring and capability complications, necessitate a paradigm shift. To clear up this trouble, a clever fixator design imbued with the transformative energy of Aware, Sensing, Smart, and Active (ASSA) technology has been developed. This fixator transcends its passive role, evolving into a wise IoT gateway. It continuously gathers and analyses facts from numerous incorporated sensors, supplying real-time insights into the tricky dance of fracture healing. Its analytical prowess fosters computerized identification of vital activities and milestones within the affected person’s recuperation journey, empowering well-timed interventions and knowledgeable scientific selection-making. Furthermore, the fixator vigilantly monitors patient compliance, making sure adherence to prescribed behaviours and nipping non-compliance in the bud. However, its innovation extends beyond mere monitoring. Embedded within its smart framework lies a modern pain manipulation mechanism powered through a thermoelectric generator (TEG).